Reducing academic isolation in favour of learning relationships through a virtual classroom - Mike Goldrick (Association for Learning Development in Higher Education (ALDinHE), 2012)
Abstract Due to geographical distances and sporadic contact with peers and faculty members, many off-campus or distance learners experience feelings of inadequacy, reduced self-confidence and other social anxieties. As a means to reduce and avoid these consequences of academic isolation, Higher Education institutes have traditionally used asynchronous forms of communication in order to bridge these geographical gaps. However, due to advances in technology, it is now possible to offer distance learners the opportunity to communicate synchronously with their peers and their teachers as they would in a real classroom. In accordance with these developments, this research examines the development of a virtual learning support service in National College of Ireland. Using survey results, online student feedback and semester results, this research will present how the problem of academic isolation was reduced in National College of Ireland by incorporating the use of a virtual classroom. Presenting screen shots and a review of online teaching, the research will illustrate how a learning support service can become more flexible and student centred. ÃÂ